The City in History in Respect of Human and Space / İnsan ve Mekan Açısından Tarihte Şehir - Unver, Metin; Tanriverdi, Mustafa (The City's Language / Şehrin Dili / Langues de la ville, 2021)
Understanding civilized society encompasses the understanding of cities given that the urban environment, which is a natural reflection of settled life, shapes the civilization of a society. Moreover, cities enriched with the effects of trading functions as centers of modernization. At present, cities are exposed to the influence of different dynamics, which are a result of modern life. This influence plays an important role in the shaping of city life and identity. This study, which is entitled Cities in History with Respect to Humans and Spaces, highlights the transformation of cities throughout history and aims to examine the histories of important cities from the social, cultural, political, and economic perspectives. The study emerges as a result of a meticulous evaluation of original scientific writings in urban history and aims to contribute to research in this field. First, the paper presents an examination of the effect of football on urban identity followed by discussions on the tales of cities penned by Ottoman geographers, the transformation of cities previously dominated by wooden buildings and the impact of fires, the identity of cities under the influence of ideologies, the role of squares in the identification of cities, the role of foundations in shaping city identity, and the effects of asitane, dargah, and khanqah structures in the formation of the social identity of cities.